Renal Peripheral Neuroectodermal Tumor Presenting at Age 78: Case Report - Michelle E. Koski; Jason M. Tedesco; Peter E. Clark (The Scientific World Journal)
Primitive neuroectodermal tumor (PNET) of the kidney is a rare and aggressive tumor, often presenting in advanced stages and progressing rapidly. Renal PNET (rPNET) may affect a wide age spectrum, but the majority of cases are in young adults. We present a case of advanced rPNET in a 78-year-old woman. To our knowledge, this is the most advanced age of presentation of this neoplasm to date. We report on her presentation and management, and discuss the current clinical management of this tumor.